Geographical distribution, host range and genetic diversity of Fusarium oxysporum f. sp. cubense causing Fusarium wilt of banana in India - Thangavelu, Raman; Amaresh, Hadimani; Gopi, Muthukathan; Loganathan, Murugan; Nithya, Boopathy; Devi, Perumal Ganga; Anuradha, Chelliah; Thirugnanavel, Anbazhagan; Patil, Kalyansing Baburao; Blomme, Guy; Selvarajan, Ramasamy (MDPI, 2024)
Fusarium wilt of banana is a major production constraint in India, prompting banana growers to replace bananas with less remunerative crops. Effective disease management practices thus need to be developed and implemented to prevent further spread and damage caused by Fusarium oxysporum f. sp. cubense (Foc), the cause of Fusarium wilt. Currently, knowledge of disease incidence, affected varieties, and the geographical spread of Foc races in India are only scantily available. An extensive field survey was conducted in 53 districts of 16 major banana-growing states of and one union territory of India that covered both tropical and subtropical regions. Disease incidence ranged from 0 to 95% on farms, with Cavendish bananas (AAA) most affected. No Fusarium wilt symptoms due to Foc R1 were observed in Nendran (AAB) or Red Banana (AAA) in South India. During the survey, 293 Foc isolates were collected from Cavendish, Pisang Awak (ABB), Silk (AAB), Monthan (ABB), Ney poovan (AB), and Mysore (AAB) bananas. Isolate diversity was assessed through Vegetative Compatibility Group (VCG) analyses, sequencing of EF1α gene sequences, phylogenetic analyses, and characterisation by SIX gene composition. Thirteen VCGs were identified, of which VCGs 0124, 0125, 01220, and 01213/16 were dominant and infected Cavendish bananas. Phylogenetic analysis divided the Indian Foc isolates into race 1 (R1), subtropical race 4 (STR4), and tropical race 4 (TR4). Secreted in Xylem (SIX) gene analyses indicated that the effector genes SIX4 and SIX6 were present in the VCGs 0124, 0124/5, 0125, and 01220 of race 1, SIX7 was present only in Foc STR4, and SIX8 was found only in Foc R4 (TR4 and STR4) isolates. Insights into the geographical distribution of Foc races, and their interactions with banana varieties, can guide integrated disease management intervention strategies across India.